(untitled) - Gahart,Betty L. (St. Louis, Mo., 2006)
Updated annually, this invaluable resource has been the preferred IV drug reference for over 30 years. More than 350 drugs are listed A to Z by generic name and cross-referenced by trade and generic name, so information on every drug is available in seconds. New monographs for approximately 10 IV drugs recently approved by the FDA provide the most current IV drug information, while hundreds of new and updated facts ensure that practitioners are kept up to date on every drug theyre likely to administer.
Keywords: Intravenous therapy,Nursing,Phương pháp điều trị trong tĩnh mạch; Handbooks, manuals, etc